Compressible cellulose nanofibril (CNF) based aerogels produced via a bio-inspired strategy for heavy metal ion and dye removal. (15th March 2019) - Tang, Juntao; Song, Yang; Zhao, Feiping; Spinney, Stewart; da Silva Bernardes, Juliana; Tam, Kam Chiu
Graphical abstract: Highlights: Bioinspired strategy to prepare lightweight, compressible CNF based aerogels. Aerogels exhibited good adsorption capacity towards Cu (II) and methyl orange. X-ray microtomography revealed the distribution of Cu (II) in aerogels. Abstract: A sustainable nanomaterial, cellulose nanofibril (CNF) was used to prepare aerogel sorbents to remove various contaminants in wastewater. A mussel-inspired coating strategy was used to introduce polydopamine onto the surface of CNFs, which were cross-linked with polyethylenimine (PEI) to form the aerogels. The synthetic procedure was optimized to achieve a minimal consumption of raw materials to produce a robust porous structure. The aerogels possessed a low density (25.0 mg/cm 3 ), high porosity (98.5%) and shape recovery in air and water. Adsorption studies were conducted on two representative contaminants, Cu (II) and methyl orange (MO). The kinetic data obeyed the pseudo 2 nd order kinetic model and the mechanism of adsorption could be described by the intra-particle diffusion model. The Langmuir model fitting yielded a maximum adsorption capacity of 103.5 mg/g and 265.9 mg/g for Cu (II) and MO, respectively. The effects of pH on the adsorption performance were evaluated, confirming that the aerogels can maintain a high adsorption capacity over a wide pH range.